Opioid-free strategies for patient-controlled intravenous postoperative analgesia: a review of recent studies - Luo, Xin; Rao, Pan-Guo; Lei, Xing-Heng; Yang, Wen-Wen; Liao, Bao-Zhen; Guo, Rui (Frontiers in Pharmacology, 2024)
Postoperative pain management has consistently been a critical topic in the medical field, with patient-controlled intravenous analgesia (PCIA) being one of the most commonly utilized methods for postoperative analgesia. Currently, opioids remain the primary choice for PCIA in clinical practice. However, in recent years, an increasing number of studies have explored analgesic strategies aimed at reducing or eliminating the use of opioids in PCIA to mitigate the associated side effects and dependence. This article systematically reviews the progress of research on opioid-free analgesic strategies in PCIA through a comprehensive analysis of relevant literature.